Efforts to Advance Multi-Organ Transplantation in the Philippines - 奥村, 晋也; 波多野, 悦朗; Michaela, Liquete; 小木曾, 聡; 山根, 佳; 平尾, 浩史; 伊藤, 孝司; 楊, 知明 (移植, 2024)
BACKGROUND The Philippines initiated organ transplantation (Tx) in the 1960s with its first deceased donor kidney transplant (KT). Significant milestones include the first simultaneous kidney and pancreas Tx from a deceased donor and the first deceased donor liver transplant (LT) in 1988 and the first living donor LT in 1996. Despite these early advancements, the country's Tx efforts have predominantly focused on kidneys, leaving other organ Tx programs underdeveloped.OBJECTIVESTo examine factors affecting this limited progress in multi-organ Tx and suggest improvements.METHODSData were gathered from the Philippine Renal Registry/Human Organ Preservation Effort. RESULTSApproximately 500 KTs are performed annually, mostly from living donors. LT, however, is restricted to three centers, leading many patients to seek Tx abroad and resulting in limited local program awareness. The Philippines also faces a global organ shortage, with only 50 deceased donors between 2019 and 2022.DISCUSSIONThe presentation will explore ongoing initiatives to enhance multi-organ Tx in the Philippines, addressing various social, cultural, religious, and economic challenges.